Nonlinear diffusion process in a Bénard system at the critical point for the onset of convection - Kraenkel, R. A. [UNESP]; Kurcbart, S. M. [UNESP]; Pereira, J. G. [UNESP]; Manna, M. A. (American Physical Society (APS), 1993)
The evolution equation governing surface perturbations of a shallow fluid heated from below at the critical Rayleigh number for the onset of convective motion, and with boundary conditions leading to zero critical wave number, is obtained. A solution for negative or cooling perturbations is explicitly exhibited, which shows that the system presents sharp propagating fronts. © 1993 The American Physical Society.